Household’s willingness to pay for malaria medical treatment in Ibarapa East local government area of Oyo State, Nigeria (2012)
Malaria is a disease that has negatively affected livelihood of many households in Nigeria. This study analyzed the factors influencing households’ willingness to pay for medical treatment of malaria by selected rural households in Oyo state. The data were collected with structured questionnaires that were administered to households using multi-stage sampling method. Data analysis was done with descriptive statistics and Logit regression. Results show that 16.9% of the respondents are willing to pay below or exactly W500 for malaria treatment using insecticides, 18.1% of the respondents are willing to pay between N-1000 <N2000 for malaria treatment using insecticide treated nets and 20.5% of the respondents are willing to pay 141000 <-N-2000 for malaria treatment using hospital treatment. Willingness to pay for medical treatment of malaria is positively influenced by gender, primary education, tertiary education, cost of malaria, awareness about malaria and income (p<0.05) and negatively related to lost work days due to malaria (p<0.01).